The employment of multimedia elements in classroom teaching among TESL Teacher-trainees in University Malaysia Sabah - Amanda Hollygrace Peter; Wardatul Akmam Din (Penerbit UMS, 2023)
The employment of multimedia in classroom teaching has pushed education into one step higher from the conventional approach teaching method to more participatory and exciting teaching and learning process. The purpose of this research is to explore the degree to which multimedia is used in classroom instruction among TESL teacher-trainees during the practical teaching. A total of 37 respondents comprising of fourth year TESL teacher-trainees from University Malaysia Sabah participated. This study also aims to find out whether or not the TESL teacher-trainees integrate multimedia in classroom teaching and if they do, the study aims to identify the multimedia elements they frequently use and if not, the study wants to find out the reasons for not integrating multimedia in their classroom teaching. As a result, it was observed that even among those that integrate multimedia, there are limitation to using multimedia in the classroom activity. Furthermore, the advantages stemming from the integration of multimedia have also been discovered. The result of the data analysis revealed three major findings namely the forms of multimedia incorporated in classroom teaching by TESL teacher-trainees, the benefits of the integrating multimedia in the classroom and the limitations. Based on the results, numerous discussions and suggestions are formed in order to enhance the incorporation of multimedia in classroom education